Saint Olav's Axe: Norwegian Church Treasures, Diplomacy and Exile during the Early Reformation - Sicking, Louis, (Late Antiquity and Medieval Studies E-Books Online, Collection 2026, 2025)
Embark on a thrilling journey into one of Norway's greatest historical mysteries! In 1537, amidst a power struggle and religious upheaval, Norway's last Catholic archbishop flees to the Habsburg Netherlands, taking treasures from Nidaros Cathedral-St. Olav's axe, crowns, golden chalices, and sacred relics. Some vanish in diplomatic disputes, others are lost at sea or seized by pirates. But where did they all end up? Drawing on rare archival discoveries, this book uncovers a riveting tale of exile, diplomacy, and lost heritage. Packed with vivid storytelling and fresh insights, it reveals the dramatic fate of Norway's sacred treasures at the dawn of the Reformation.